Workplace Adversity: can a person-centred approach improve resilience in student midwives? - Lee, Barbara (2014)
Abstract Aim: This study considers how student midwives survive and thrive in the face of workplace adversity. It explores key factors for success and failure and identifies how a person-centred approach might improve resilience in student midwives. The focus is on the student midwife’s experiences within clinical placements in the NHS.